2016
DOI: 10.1021/acs.jproteome.6b00400
|View full text |Cite
|
Sign up to set email alerts
|

Looking for Missing Proteins in the Proteome of Human Spermatozoa: An Update

Abstract: The Chromosome-Centric Human Proteome Project aims to identify proteins classed as « missing » in the neXtProt knowledgebase. In this article, we present an in-depth proteomics analysis of the human sperm proteome to identify testis-enriched missing proteins. Using a range of protein extraction procedures and LC-MS/MS analysis, we detected a total of 235 proteins (PE2-PE4) for which no previous evidence of protein expression was annotated. Through a combination of LC-MS/MS and LC-PRM analysis, data mining and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 43 publications
4
92
0
Order By: Relevance
“…Furthermore, the CFAP69 protein was also identified as a testis-enriched protein using an in-depth proteomics analysis in human spermatozoa 22. The orthologue of CFAP69 in Chlamydomonas reinhardtii is FAP69 (flagellar protein 69), a 135 kDa protein containing two armadillo repeat domains 23 24.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the CFAP69 protein was also identified as a testis-enriched protein using an in-depth proteomics analysis in human spermatozoa 22. The orthologue of CFAP69 in Chlamydomonas reinhardtii is FAP69 (flagellar protein 69), a 135 kDa protein containing two armadillo repeat domains 23 24.…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds of PE2,3,4 MPs have been detected in sperm and testis, led by the Chromosome 2/14 consortium in Switzerland and France 12,13 and the Chromosome 1 team in China. 14,15 Sun et al 16 identified 11 558 proteins in testis using SDS-PAGE fractionation, digestion with a combination of the proteases trypsin, LysC, and GluC, and high-pH reverse-phase fractionation; this total is 3700 more proteins than the previous year.…”
Section: Progress On the Credible Detection Of Nextprot Pe234 Missimentioning
confidence: 99%
“…4 This also emphasizes the difficulty in closing the human proteome gap with high-quality unambiguous MS data and the necessity for further targeted orthogonal studies and strategies to reveal shy proteins. Vandenbrouck et al 15 started with 235 missing protein candidates in spermatozoa, of which 206 met the HPP guidelines v2.1. Some were confirmed with immunohistochemistry, such as orphan proteins CXorf58 and C19orf81.…”
Section: Choosing the Tissues Most Likely To Be Expressing Missing Prmentioning
confidence: 99%
“…As noted above, SRMs were used very effectively by Vandenbrouck et al 15 to confirm missing protein identifications in testis, and they are at the heart of the targeted approach for detecting the 40 missing proteins proposed by Duek et al 10 SRMs were also used by Zhao et al 16 to confirm missing proteins identified in the membrane enrichment studies. Poverennaya et al 21 from the Chromosome 18 team used stable isotope-labeled standards for SRM (SRM/SIS) analyses, as well as shotgun LC–MS/MS, of normal liver and HepG2 liver cells.…”
Section: Selected Reaction Monitoring Mass Spectrometry For Targeted mentioning
confidence: 99%